Strategi Guru Pendidikan Agama Islam Meningkatkan Religiusitas Siswa Di Madrasah Ibtidaiyah Adikarso Kebumen - Ida Farida; Mustajab Mustajab; Fibriyan Irodati (IAINU Kebumen, 2023)
This study aims to describe the strategies of Islamic religious education teachers in increasing the religiosity of students at Madrasah Ibtidaiyah Ma'arif Adikarso. Describe the inhibiting factors and teacher solutions in increasing student religiosity at Madrasah Ibtidaiyah Ma'arif Adikarso. To achieve the above research objectives, researchers used a qualitative approach. The research design used was descriptive research with the type of field research located at Madrasah Ibtidaiyah Ma'arif Adikarso Kebumen. Data in this study were collected using interviews, observation and documentation. The results of the study, it was concluded that the strategy of Islamic religious education teachers in increasing the religiosity of students at Madrasah Ibtidaiyah Ma'arif Adikarso Kebumen is to improve the quality of Islamic religious education learning (the Qur'an hadith, aqidah morals, jurisprudence and skiing) in classes that use several ways namely (education by example, advice, punishment and habituation) and the second is developing Islamic religious education learning through religious activities such as tadarus al-Qur'an, ziaroh, infaq, Ramadan activities (opening and tarawih together) and zakat fitrah. The inhibiting factors in increasing religiosity are two factors, namely internal factors, namely the establishment of long-distance/online schools. And external factors, including family background, the influence of the student playing environment, and the negative influence of technology. The solution taken in dealing with these obstacles is to optimize existing technology, utilize existing facilities at schools and build cooperation with parents/guardians of students.